Systemic Air Embolism in a Patient With Lung Lesion Undergoing Neurosurgery in Sitting Position: A Case Report. Issue 6 (April 2020) - Joys, Steve; Podder, Subrata; Salunke, Pravin; Jangra, Kiran
Abstract : Systemic air embolism secondary to venous air embolism is a known complication of sitting position surgery. However, the possibility of an isolated systemic air embolism must be considered, especially in patients with preexisting lung disease receiving positive pressure ventilation. These patients may benefit from a comprehensive preoperative evaluation and advanced intraoperative monitoring. We report a case of a 53-year-old woman with chronic obstructive airway disease and a preexisting fibrocavitary lung lesion, who developed isolated air entrainment into the left heart during sitting position surgery. Abstract : Supplemental Digital Content is available in the text.